Behind the beautiful forevers - Boo, Katherine (Random House Trade Paperbacks, 2014)
Profiles everyday life in the settlement of Annawadi as experienced by a Muslim teen, an ambitious rural mother, and a young scrap metal thief, illuminating how their efforts to build better lives are challenged by religious, caste, and economic tensions.